2009
DOI: 10.1021/nn900167p
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Growth, Microstructure, and Field-Emission High-Performance of Ultrathin Diamond Nanorods

Abstract: We report the growth of ultrathin diamond nanorods (DNRs) by a microwave plasma assisted chemical vapor deposition method using a mixture gas of nitrogen and methane. DNRs have a diameter as thin as 2.1 nm, which is not only smaller than reported one-dimensional diamond nanostructures (4-300 nm) but also smaller than the theoretical value for energetically stable DNRs. The ultrathin DNR is encapsulated in tapered carbon nanotubes (CNTs) with an orientation relation of (111)diamond//(0002)graphite. Together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 50 publications
3
94
0
6
Order By: Relevance
“…Shang et al reported the growth of ultrathin diamond nanorods (UDNRs) by a MPCVD method (in N 2 /CH 4 plasma) [84]. As-deposited UDNRs have a length of 50-300 nm and a thin diameter of 2.1 nm, less than the theoretical minimum value (2.7 nm) for energetically stable UDNRs [82,83].…”
Section: Microwave Plasma Enhanced Cvd (Mpcvd) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shang et al reported the growth of ultrathin diamond nanorods (UDNRs) by a MPCVD method (in N 2 /CH 4 plasma) [84]. As-deposited UDNRs have a length of 50-300 nm and a thin diameter of 2.1 nm, less than the theoretical minimum value (2.7 nm) for energetically stable UDNRs [82,83].…”
Section: Microwave Plasma Enhanced Cvd (Mpcvd) Methodsmentioning
confidence: 99%
“…This value is extremely high. Shang et al reported the growth of ultrathin diamond nanorods (DNRs) by a microwave plasma assisted chemical vapor deposition method, using a mixture gas of nitrogen and methane [84]. DNRs have a diameter as thin as 2.1 nm, which is not only smaller than reported one-dimensional diamond nanostructures (4-300 nm) but also smaller than the theoretical value for energetically stable DNRs.…”
Section: Electron Field Emission (Efe) From Planar Diamond Nanowire Amentioning
confidence: 99%
“…[104] Die UNCD-Filme werden in einem Mikrowellenplasma-CVD-Reaktor in Ar/CH 4 /H 2 /N 2 -Gemischen auf Si-Substraten abgeschieden. [105] Die Kerne der Diamant-Nanodrähte ("diamond nanowires", DNWs) haben Durchmesser von 5-6 nm und wachsen entlang der [110]-Richtung. Die experimentellen Ergebnisse zeigten in Übereinstimmung mit Ergebnissen von Arenal et al, [106] dass N 2 eine wichtige Rolle bei dem Wachstum drahtartiger Diamantkçrner spielt.…”
Section: Cvd Mit Aao-templatunclassified
“…[110] Die frisch abgeschiedenen UDNRs haben eine Länge von 50-300 nm und einen Durchmesser von nur 2.1 nm, was unter dem theoretischen Mindestwert (2.7 nm) für energetisch stabile UDNRs liegt. [25,27] Es wird vorgeschlagen, dass das Wachstum der UDNRs einem heterogenen selbstkatalytischen Gasphase-Flüssigkeit-Mechanismus folgt.…”
Section: Cvd Mit Aao-templatunclassified
See 1 more Smart Citation